2013
DOI: 10.1186/1471-2148-13-55
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of bone compactness in extant and extinct moles (Talpidae): exploring humeral microstructure in small fossorial mammals

Abstract: BackgroundTalpids include forms with different degree of fossoriality, with major specializations in the humerus in the case of the fully fossorial moles. We studied the humeral microanatomy of eleven extant and eight extinct talpid taxa of different lifestyles and of two non-fossorial outgroups and examined the effects of size and phylogeny. We tested the hypothesis that bone microanatomy is different in highly derived humeri of fossorial taxa than in terrestrial and semi-aquatic ones, likely due to special m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 42 publications
2
62
0
Order By: Relevance
“…By contrast, limb epiphyseal sutures are consistently fused in the skeletal specimens of Notoryctes typhlops and N. caurinus that we have examined, but these all appear to be adults based on the presence of a fully erupted permanent dentition (juvenile specimens of Notoryctes are exceptionally rare in scientific collections). Consistent closure of the epiphyseal sutures in the limbs of Notoryctes adults (which contrasts with the condition observed in most other marsupial species; Geiger et al 2014) may reflect the high mechanical loadings their limbs are subjected to during digging; however, we note that Geiger et al (2014) examined both fossorial and non-fossorial mammals and found no clear relationship between locomotor mode and the sequence of epiphyseal closure (see also Meier et al, 2013).…”
Section: Anatomical Descriptionmentioning
confidence: 41%
See 1 more Smart Citation
“…By contrast, limb epiphyseal sutures are consistently fused in the skeletal specimens of Notoryctes typhlops and N. caurinus that we have examined, but these all appear to be adults based on the presence of a fully erupted permanent dentition (juvenile specimens of Notoryctes are exceptionally rare in scientific collections). Consistent closure of the epiphyseal sutures in the limbs of Notoryctes adults (which contrasts with the condition observed in most other marsupial species; Geiger et al 2014) may reflect the high mechanical loadings their limbs are subjected to during digging; however, we note that Geiger et al (2014) examined both fossorial and non-fossorial mammals and found no clear relationship between locomotor mode and the sequence of epiphyseal closure (see also Meier et al, 2013).…”
Section: Anatomical Descriptionmentioning
confidence: 41%
“…philcreaseri was semiaquatic (Canoville and Laurin, 2010). However, a recent study of bone compactness in the humeri of talpids found no significant difference between fossorial and semiaquatic taxa (Meier et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…The phylogeny presented here is the first published analysis of multiple extinct talpids using a cladistic methodology. A recent paper by Meier et al (2013) featured a composite phylogeny that positioned a number of extinct talpids in an extant phylogeny based on the taxonomic opinions expressed in the paleontological literature (e.g., Hutchison, 1974;Ziegler, 1999) rather than cladistics. S anchez-Villagra et al (2004) provided character codes for the humeri of 18 extinct talpid taxa, but never presented an analysis of these data.…”
Section: Discussionmentioning
confidence: 99%
“…To supplement our sample, we included a published cortical bone profile of the humerus from the bat Myotis myotis (Meier et al, 2013) as well as profiles scanned by microCT representing nine avian taxa (Simons, Hieronymus & O’Connor, 2011; ELR Simons, 2008, unpublished data). Cortical bone profiles were processed using BoneJ for ImageJ to calculate the cross-sectional geometric parameters of each specimen (Table 1).…”
Section: Methodsmentioning
confidence: 99%